2008
DOI: 10.1002/0471142301.ns0929s44
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Inhalation of Alcohol in Rats

Abstract: Alcohol dependence constitutes a neuroadaptive state critical for understanding alcoholism, and various methods have been utilized to induce alcohol dependence in animals, one of which is alcohol vapor exposure. Alcohol vapor inhalation provides certain advantages over other chronic alcohol exposure procedures that share the ultimate goal of producing alcohol dependence in rats. Chronic alcohol vapor inhalation allows the experimenter to control the dose, duration, and pattern of alcohol exposure. Also, this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 44 publications
(56 reference statements)
5
155
0
1
Order By: Relevance
“…These can involve passive induction of dependence (318) or IA to voluntary consumption of alcohol (286). Several studies have reported that previous experience with alcohol leads to higher initial levels of consumption and increased preference (315,319,320). This supports our finding that rats with previous experience with operant alcohol self-administration consumed more alcohol and had higher preference for alcohol compared with controls in the IA two-bottle free choice preference drinking model.…”
Section: A History Of Operant Self-administration Resulted In Increassupporting
confidence: 89%
“…These can involve passive induction of dependence (318) or IA to voluntary consumption of alcohol (286). Several studies have reported that previous experience with alcohol leads to higher initial levels of consumption and increased preference (315,319,320). This supports our finding that rats with previous experience with operant alcohol self-administration consumed more alcohol and had higher preference for alcohol compared with controls in the IA two-bottle free choice preference drinking model.…”
Section: A History Of Operant Self-administration Resulted In Increassupporting
confidence: 89%
“…3 Chronic alcohol inhalation through continuous exposure in a vapour chamber was found to be the most effective way to induce alcohol dependence in rodents. 4 …”
Section: The Addictive Potential Is Unknownmentioning
confidence: 99%
“…Upon cessation of alcohol vapor exposure, animals exhibit signs of tolerance and physical dependence and may be tested for a multitude of motivational, acute withdrawal-and protracted abstinence-related behaviors. 21 Gilpin et al 15 exposed rats to alcohol vapor for 4 hours and measured alcohol concentration in brain dialysates and blood samples collected from the tail vein at 30-minute intervals during the 4-hour exposure, as well as 8 hours following termination of alcohol vapor exposure. They found that the maximum levels of alcohol attained in blood and brain during vapor exposure were 208615 mg/ dL and 215625 mg/dL respectively.…”
Section: Alcohol Vapormentioning
confidence: 99%
“…Previous studies using the chronic intermittent alcohol vapor model showed that motivational symptoms of dependence are present in rats at acute withdrawal time points, as evidenced by increased anxiety-like behavior, increased alcohol drinking, and increased willingness to work for alcohol early during acute withdrawal, even when animals still have alcohol in their blood from vapor exposure. [21][22][23][24][25] All animal models of alcohol dependence are, in fact, models of components of alcohol dependence.…”
Section: Alcohol Vapormentioning
confidence: 99%